Rituais totêmicos e práticas educativas de um candomblé Ketu em Fortaleza - Barbosa, Madelyne dos Santos (2018)
The purpose of this study is to identify non-formal and informal educational practices, which are transcurrent in the daily ritual of a Candomblé terreiro in Fortaleza. Perceiving the moment in which the religious making is fused in educational praxis, and that make the Afro-Brazilian terreiro a constructor space of knowledge, legitimized by the oral tradition and the ancestral memory. It is, therefore, a qualitative research, ethnographic approach that used as a data construction tool the case study. Thus, the study had access to the smaller ones that surround a ritual religious tradition of millennia. The observations, the notes in the field book, the image records, and the interlocutions granted by the subjects of the research: Mr. Lagos, Mãe Ilesá and Ogan Ibadan minuden a more refined understanding regarding the conceptions of the religious and educational practices of a temple of Candomblé. The results presented in this research: The Ritual of the Orô for Exu and the ritual of the Ebó appear in details, speeches and situations. The animal sacrifice for Exu here is thought of as totemism, in a totemic relation that is established in the act of offering the animals by means of sacred immolation to the Orixás. And the Ebó Ritual is shown in all depth in Mr. Lagos' case. In this way, the two rituals are situated in the study as elements of Yoruba tradition and, especially as the moment that the terreiro produces non-formal education. Teaching religious foundations and perpetuating an established tradition.